PENGARUH KANDUNGAN MINERAL PADA TANAH PASIR TERHADAP NILAI CBR TANAH - Adam Dwi Rahmanto; Sri Wulandari (Jurnal Jalan-Jembatan, 2020)
Value of CBR is important in the planning of road pavement. Meanwhile, the CBR value of a material is very diverse and not necessarily the landfill material with a CBR value that meets specifications available easily and quickly. Therefore results of this study are expected to be a reference in determining which sand should be used for a road foundation if mineral content is known. This study was conducted by taking 3 sand samples from 3 different locations (Depok, Indramayu, and Tangerang). These samples were tested to determine physical properties, mechanical properties and mineral content. Based on the results of the particle size distribution analysis, we can see the effect between the percentage of clay and silt with the CBR value of each sand sample. The less the clay and the silt content in the sand sample, the smaller the CBR value obtained. While based on the results of x-ray diffraction testing, it can be concluded that the dominant SiO2 and Fe2O3 minerals can be approved to increase the CBR value. This is consistent with the level of Mohs hardness of these minerals, because the level of hardness of two minerals is the highest among other minerals contained in all samples. So, it can also be concluded that if a sand contains minerals with a high level of Mohs hardness, the greater CBR value of sand can be obtained.Keywords: soil investigation, sand, CBR, mineral content, x-ray diffraction.